A Kinetic Study on Corn Gluten Hydrolysis - Apar, Dilek Kilic; Ozbek, Belma (WILEY-V C H VERLAG GMBH, 2009)
In the present study, the hydrolysis of corn gluten was performed by using two commercial enzymes, Protamex and PTN, to investigate the reaction kinetics. The reactions were carried out for 10 min in 0.1 L of aqueous solutions containing 10, 20, 30 and 40 g protein L-1 corn gluten at various temperature and pH values. The progress of the reactions was monitored by a pH-stat method. It was found that the kinetics of corn gluten hydrolysis by Protamex and PTN obey the Michaelis-Menten model and higher catalytic yields were obtained with Protamex than PTN at all of the experimental conditions applied.
Keywords: Alcalase; Corn gluten; Hydrolysis; Kinetics; ENZYMATIC MODIFICATION; WHEY PROTEINS; MODEL; IMPROVEMENT; AGAROSE; Engineering